Principles of macroeconomics - Agba, Akomaye V. (Lagos: Nigeria: Concept Publications Ltd., 1994)
This book provides a teaching material, a study companion and a readable material for the professional economist. Topics covered include: national income accounting; national income determination; money and interest rate; consumption theory; unemployment; foreign trade; inflation; multilateral financial institutions; and structural adjustment programme (SAP).
Includes index
lje 22/08/16
Loan
Keywords: Macroeconomics